Some stylized facts of the informal sector in Brazil in the 1980's end 1990's - Fabio Veras Soares (Institute for Applied Economic Research (ipea), 2015)
Two facts have characterized the evolution of the informal sector in Brazil during the last two decades: the increase in the proportion of non-registered workers and the diminishing wage gap between non-registered and registered workers. In this paper, we briefly review the literature on informal sector in developing countries and document both the increase of the informal sector and the fall in the wage gap in Brazil. Besides, we investigate which factors were responsible for the fall in the wage gap and how this reduction has contributed to reduce wage inequality between 1981 and 1999. Among our findings, we would highlight: i) the coincidence between these two movements and the market-oriented reforms of the early 1990's; ii) that the fall in the formal/informal wage gap has substantially contributed to the decrease in wage inequality. After education, the fall in the wage premium due to the possession of a work-card was the main responsible for bringing down wage inequality. Why and how it happened is an open debate. We will tackle this issue on two forthcoming papers were we investigate the role of the trade liberalization (Soares, 2004a) and the effects of the increasing indexation of informal sector wages to the minimum wage (Soares, 2004b).
Keywords: 330